Determining the optimum process mean in a two-stage production system based on conforming run length sampling method. Issue 6 (2nd November 2018) - Fallah Nezhad, Mohammad Saber; Farsani, Zahra Davoodi
Abstract: We develop a profit optimization model based on Markovian approach to determine the optimum process mean in the two-stage serial production system. If quality characteristics of the items fall within the specification limits then the items are accepted. Our inspection approach in sampling plan is that when the number of conforming items between successive defective items falls below the lower control threshold, then the batch is rejected, and if it falls above the upper control threshold, then the batch is accepted and if it falls within the control thresholds then the process of inspecting the items continues. Taguchi's symmetric quadratic quality loss function is applied for evaluating the product quality. Then a numerical example is provided to demonstrate the application of proposed model. Also a sensitivity analysis of the model is provided.